2003
DOI: 10.1242/jeb.00547
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature on swimming performance and oxygen consumption in adult sockeye (Oncorhynchus nerka) and coho (O. kisutch)salmon stocks

Abstract: . (2003). The effect of temperature on swimming performance and oxygen consumption in adult sockeye (Oncorhynchus nerka) and coho (O. kisutch) salmon stocks. J. Exp. Biol. 206,[3239][3240][3241][3242][3243][3244][3245][3246][3247][3248][3249][3250][3251] In both the on-line and printed versions of this paper, some of the equations in the legends to Figs 2-4 were printed incorrectly.On page 3245, in the legend to Fig.·2, the two equations should read:M O 2 routine =2.12+0.09e 0.18t (ambient; broken line) and M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
456
5
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 428 publications
(488 citation statements)
references
References 44 publications
25
456
5
2
Order By: Relevance
“…Average water temperatures in the Seton River were 16.38C and 15.08C during the months of August and September, respectively. These values are very close to the optimal temperature for aerobic scope in adult Gates Creek Lee et al 2003). Thus, the environmental conditions experienced by the sampled fish in 2005 may have minimized migration-related stress, particularly in the lead up to capture at Seton River Dam.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Average water temperatures in the Seton River were 16.38C and 15.08C during the months of August and September, respectively. These values are very close to the optimal temperature for aerobic scope in adult Gates Creek Lee et al 2003). Thus, the environmental conditions experienced by the sampled fish in 2005 may have minimized migration-related stress, particularly in the lead up to capture at Seton River Dam.…”
Section: Discussionsupporting
confidence: 52%
“…Water temperatures were slightly cooler (an average decline of ;28C) during the lowest, and final, discharge period, yet passage time was the same as that observed during the highest, and first, discharge period. The fact that water temperatures throughout the study were close to the optimal range for maximum aerobic scope in adult Gates Creek sockeye salmon (Lee et al 2003) may partially explain this lack of effect, and why fish were in relatively good physiological condition following passage. Although there was a seasonal decline in discharge in both the Fraser and Seton rivers, there did not appear to be an interaction between temperature and discharge, suggesting that seasonal changes in river flow and temperature did not confound our results.…”
Section: Discussionmentioning
confidence: 97%
“…EPOC is a measure of the capability to recover from fatigue and is positively related to anaerobic respiration (Lee et al 2003b, Fu et al 2009). It has been reported that EPOC is associated with circulating catecholamine and the gluconeogenic-glycolytic and triglyceride-fatty acid cycles (Gaesser & Brooks 1984, Bahr 1992.…”
Section: Epoc Anaerobic Swimming and %U Critmentioning
confidence: 99%
“…Sockeye adults migrating through the Columbia and Snake River mainstem were generally exposed to temperatures that exceeded their assumed 15 o C optimum for physiological and swimming performance (Brett, 1995;Lee et al, 2003). However, temperature observations at several dams indicate that sockeye never encountered lethal temperatures (>24 o C, Servizi and Jensen, 1977).…”
Section: Annual and Seasonal Effects Of Temperature On Sockeye Migrationmentioning
confidence: 99%